Free pedagogies and emotional self-regulation: anti-authoritarian notes on education - Ponce-León, Juan José (2021)
This article aimed to study the relationship between emotional self-regulation and free pedagogies. To do this, an extensive literature review was presented and a critical theoretical debate was raised about the limits of traditional education and its negative impact on children's mental health. The results show that, on the one hand, emotional self-regulation is a good predictor and protective factor against psychopathologies, and, on the other hand, that alternative education shows clinically significant impacts on the development of emotional self-regulation and, consequently, higher rates of satisfaction with life, proactive behaviors and fewer antisocial behaviors. In addition, traditional education shows a low level of socio-affective development in childhood.